Perceptions of Children's Participation in Their Healthcare: A Critical Review. (3rd July 2015) - Davies, Adam; Randall, Duncan
Abstract : Key policies at national and international levels have called for the increased involvement of children in their healthcare. This reflects a growing recognition of the sociology of childhood and of children as social agents. However, it seems that the involvement agenda has met with mixed results, with children often being left marginalized as a result of professional, parental, and other factors. A need for further research into children and health professional's attitude towards child involvement has been identified by research in this area. In this article we review the current literature on children's involvement in care, noting the differences between professional views and those of children themselves. To do this we used a literature review, incorporating electronic database searching and snowballing techniques. We found that children and health professionals are in general agreement that children should be involved in their healthcare; however there is some disagreement over the extent of involvement. Many children experienced exclusion due to many factors including parental role, in that there may be a belief among adults that children cannot act in their own best interest. The involvement of children in their healthcare may be considered transitory and dependent upon competing factors. It may be helpful to view child involvement in healthcare in the context of children's status in their society. Health professionals should aim to empower children with appropriate information about their healthcare.